What is and what is not nursing care? - Hidalgo Mares, Brenda (2020)
The analysis of the nursing situation is established within the question what is and what is not nursing care ?, from the philosophical and paradigmatic perspective of Leonardo Boff of the ways of being in the world and the socio-cultural context of Florence , which aims to give a meaning or interpretation from an epistemological and ontological position, that is, from the nursing phenomenology. Establishing then that nursing is not only science or art, but a science-art of common sense, with intuition, identity and singularity, likewise; care is given at an opportune moment, in the accompaniment of the other, within a coexistence that develops with dignity, which gives rise to complex, sensitive, supportive, kind and connected human beings with everything and everyone in the universe. Without care, the human being would become inhuman, because the human being is the epistemological object of nursing. Which leads to the challenge, to reconcile the two-modes-of-being: work and care, from materiality being the dominant mode-of-being-work, then seeking a balance with spirituality, mode-of-being-care .